Test-Retest Reliability of the Sanet Vision Integrator. - Baas, Eric A.; Panchal, Naiya; Coffey, Brian; Patel, Shruti; Kelly, Susan (Optometry & Visual Performance, 2016)
Background: The visual system plays a crucial role in successfully accomplishing most sports activities, not only for professional athletes but also at lower levels of competition. The Sanet Vision Integrator (SVI) evaluates the visual guidance of motor performance by assessing the speed of motor response to visual stimuli. While the SVI is widely used clinically, the reliability and validity of the device has not been established. The purpose of this investigation was to determine the test-retest reliability of the Proaction, Reaction, and Hand Speed programs of the SVI using a control group. Methods: Twenty students at the Illinois College of Optometry (ICO), ages 22-31, performed the eye-hand tests of the SVI: Proactive, Reactive, and Hand Speed. Each subject was tested one at a time using the SVI on two consecutive visits. Visit 2 took place at least two weeks after visit 1, using identical protocols. Testing was performed under normal room illumination using a white size-50 stimulus on a black background with the subjects standing one meter away and the screen centered at chest level. Reliability was measured with the intraclass correlation coefficient (ICC). Results: The ICC was statistically significant for the Upper Left quadrant, as well as for the reaction latency of the Proactive test, the percent correct on the Reactive test, and the reaction time and hand speed of the Hand Speed test. The ICC for the Upper Right, Lower Right, and Lower Left quadrants of the Proactive test and the percent correct of the Hand Speed test were statistically insignificant. Conclusion: The Proactive, Reactive, and Hand Speed tests of the Sanet Vision Integrator can reliably measure eye-hand coordination, while other aspects of the tests are not as reliable.